2020
DOI: 10.1002/hrdq.21395
|View full text |Cite
|
Sign up to set email alerts
|

Feeling shame and guilt when observing workplace incivility: Elicitors and behavioral responses

Abstract: This research investigates the elicitors and behavioral responses associated with feeling guilt and shame in response to observed workplace incivility. We draw from the appraisal model of self-conscious emotions to hypothesize that perceiving personal responsibility for acts of incivility conducted by others in the organization is associated with feelings of guilt and shame, and that these relationships are differentially moderated by perceived controllability over the incident. We further propose that shame i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…As shame arises from the perception that the very self is flawed, it is particularly distressing and involves feeling small, powerless and exposed. To suppress such painful feelings, people avoid shame-triggering situations (Miranda, Welbourne and Sariol, 2020;Tangney, Stuewig and Hafez, 2011). Moreover, shame arises from the perception of having violated group or social norms (Efthim, Kenny and Mahalik, 2001), so it is characterized by the wish to avoid and hide from others (Tangney et al, 2011;Turner, 2014).…”
Section: Initiating Salary Negotiationsmentioning
confidence: 99%
“…As shame arises from the perception that the very self is flawed, it is particularly distressing and involves feeling small, powerless and exposed. To suppress such painful feelings, people avoid shame-triggering situations (Miranda, Welbourne and Sariol, 2020;Tangney, Stuewig and Hafez, 2011). Moreover, shame arises from the perception of having violated group or social norms (Efthim, Kenny and Mahalik, 2001), so it is characterized by the wish to avoid and hide from others (Tangney et al, 2011;Turner, 2014).…”
Section: Initiating Salary Negotiationsmentioning
confidence: 99%
“…Respondents were provided with a definition and examples of customer citizenship behavior and dysfunctional customer behavior. Respondents were then asked to recall and describe in detail their most recent experience (within the past six months) of having displayed both customer citizenship behavior and dysfunctional customer behavior at the same service provider [1], and then to complete a series of survey items based on their specific experience (Chan et al, 2019;Gong and Wang, 2021;Miranda et al, 2020). Participation was voluntary, and all respondents were assured of confidentiality.…”
Section: Studymentioning
confidence: 99%
“…Respondents were then asked to recall and describe in detail their most recent experience (within the past six months) of having displayed both customer citizenship behavior and dysfunctional customer behavior at the same service provider [1], and then to complete a series of survey items based on their specific experience (Chan et al. , 2019; Gong and Wang, 2021; Miranda et al. , 2020).…”
Section: Studymentioning
confidence: 99%
“…Ashamed feelings that stem from the perception that one's entire self is flawed may lead to higher stress and withdrawal behaviors. For instance, Miranda et al (2020) revealed that perceived responsibility for coworkers experiencing workplace incivility induced shame, which in turn led to target and instigator avoidance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%